PERAN KEPEMIMPINAN KOLEKTIF DALAM MENUMBUHKAN MODERASI BERAGAMA SANTRI: STUDI DI PESANTREN MUHAMMADIYAH DARUL ARQOM PATEAN SUKOREJO KENDAL - Muhammad, Achmad (UIN Sunan Kalijaga, 2023)
The purpose of this study was to determine the collective leadership roles implemented in the Muhammadiyah Darul Arqom Islamic Boarding School Patean Sukorejo Kendal in shaping the mindset, attitude, and behavior of religious moderation of the students. This type of research is qualitative with a descriptive model. The data obtained through observation or direct observation, supporting documents, and interviews with several key informants including leaders, teachers, and students. Data analyzed through condensation, presentation, and verification techniques. The results of this study found that the collective leadership applied at the Muhammadiyah Darul Arqom Patean Sukorejo Kendal Islamic Boarding School was quite effective in directing students to mindsets, attitudes, and behaviors that showed moderation in religion seen from a national perspective, polite attitude, openness, and accepting differences, as well as staying away from behavior violence. The leaders through exemplary direct interaction with the students and through the direction and mobilization of the teachers as well as coaching directly to the students direct the perspectives and ways of being moderate (wasathiyyah) in religion, both aspects of aqidah, worship, and muamalah. The application of habituation to the interaction of students across regional origins and levels of education strengthens the behavior of religious moderation among students.